Say 'no' to carcinogen as contraception alternative - Karen Malec (AOSIS, 2012)
A response to Correspondence to 'Dienye PO, Gbeneol PK. Contraception as a risk factor for urinary tract infection in Port Harcourt, Nigeria: A case control study. Afr J Prm Health Care Fam Med. 2011;3(1), Art. #207, 4 pages. doi:10.4102/phcfm.v3i1.207